Metal‐Free Intermolecular C−H Borylation of N‐Heterocycles at B−B Multiple Bonds. Issue 5 (22nd December 2022) - Brückner, Tobias; Ritschel, Benedikt; Jiménez‐Halla, J. Oscar C.; Fantuzzi, Felipe; Duwe, Dario; Markl, Christian; Dewhurst, Rian D.; Dietz, Maximilian; Braunschweig, Holger
Abstract: Carbene‐stabilized diborynes of the form LBBL (L= N ‐heterocyclic carbene (NHC) or cyclic alkyl(amino)carbene (CAAC)) induce rapid, high yielding, intermolecular ortho‐C−H borylation at N ‐heterocycles at room temperature. A simple pyridyldiborene is formed when an NHC‐stabilized diboryne is combined with pyridine, while a CAAC‐stabilized diboryne leads to activation of two pyridine molecules to give a tricyclic alkylideneborane, which can be forced to undergo a further H‐shift resulting in a zwitterionic, doubly benzo‐fused 1, 3, 2, 5‐diazadiborinine by heating. Use of the extended N ‐heteroaromatic quinoline leads to a borylmethyleneborane under mild conditions via an unprecedented boron‐carbon exchange process. Abstract : Carbene‐stabilized diborynes of the form LBBL (L= N ‐heterocyclic carbene or cyclic alkyl(amino)carbene) induce rapid, high yielding, intermolecular ortho‐C−H borylation at N ‐heterocycles at room temperature. The reaction initially provides the simple hydroarylated diborene, but in some cases proceeds further, providing unusual 1, 3, 2, 5‐diazadiborinine and base‐stabilized alkylidene products.